Waste PET upcycling to conductive carbon-based composite through laser-assisted carbonization of UiO-66. Issue 3 (5th January 2023) - Kogolev, Dmitry; Semyonov, Oleg; Metalnikova, Nadezhda; Fatkullin, Maxim; Rodriguez, Raul D.; Slepicka, Petr; Yamauchi, Yusuke; Guselnikova, Olga; Boukherroub, Rabah; Postnikov, Pavel S.
Abstract : The upcycling of waste polymers into novel materials with high added value is a vital task for modern chemical engineering. Abstract : The upcycling of waste polymers into novel materials with high added value is a vital task for modern chemical engineering. Here, we propose diversifying waste polyethylene terephthalate (PET) upcycling to materials with enhanced photothermal properties by laser-assisted carbonization of surface-grown UiO-66. The UiO-66 homogenous layer was formed using a solvo-thermal procedure on the surface of recycled PET sheets. The treatment by a 405 nm laser system allowed the formation of a carbonaceous layer with enhanced electrical conductivity and photothermal properties due to the presence of zirconium carbide and graphene. The developed approach opens new perspectives in the application of upcycled PET-based materials.